Multicultural Counseling Model Based on Local Wisdom in Preventing Bullying Behavior of Vocational High School Students - Lopo, Ferdinan Leonadus (Global Education Journal, 2025)
Bullying in Vocational High Schools remains a serious problem, especially in culturally diverse schools such as Kupang City. Differences in students' cultural backgrounds, accents, ethnic stereotypes, and social identities often trigger conflict and bullying behavior if not managed appropriately. Guidance and counseling services in schools play a strategic role in preventing bullying, but in practice they still tend to use a general approach and do not integrate local wisdom values. This study aims to describe and analyze a multicultural counseling model based on local wisdom in preventing bullying behavior in vocational high school students. The research method used is descriptive qualitative with data collection techniques through in-depth interviews with Guidance and Counseling Teachers and six students at SMK Negeri 6 Kupang City. The results show that individual counseling services, classical services, and conflict mediation have been implemented, but have not been structured within a multicultural counseling framework and have not utilized local wisdom values ​​of East Nusa Tenggara such as naketi, natoni, customary deliberation, mutual respect, and mutual cooperation. As a result, changes in students' attitudes and cultural sensitivity to bullying behavior have not been optimal. This study concludes that developing a multicultural counseling model based on local wisdom is crucial for increasing students' cultural awareness, empathy, and social harmony. The study's contribution is to provide a conceptual and practical basis for developing school counseling services that are contextual, culturally relevant, and effective in preventing bullying.